Blockage of neuromuscular glutamate receptors impairs reinnervation following nerve crush in adult mice - Personius, Kirkwood E.; Siebert, Danielle; Koch, Dennis W.; Udin, Susan B. (Frontiers in Cellular Neuroscience, 2022)
Motor axons in peripheral nerves are capable of regeneration following injury. However, complete recovery of motor function is rare, particularly when reinnervation is delayed. We have previously found that glutamate receptors play a crucial role in the successful innervation of muscle during mouse development. In particular, blocking NMDA receptor activity delays the normal elimination of excess innervation of each neuromuscular junction. Here, we use behavioral, immunohistochemical, electrophysiological, and calcium imaging methods to test whether glutamate receptors play a similar role in the transition from polyneuronal to mono-innervation and in recovery of function following peripheral nerve injury in mature muscle.